Knowledge Level of Women’s Reproductive Age Regarding Oral Health During Pregnancy - Ariska, Devina Nadiah; Pratiwi, Alisa Novianty; Umniyati, Helwiah (YARSI Dental Journal, 2023)
Introduction: A woman will generally experience pregnancy, which can change the health of her oral cavity. Changes that occur in gingiva are often increasing estrogen and progesterone hormones, which are combined with alteration in oral flora and decreased immune response. This occurrence can lead to gingivitis and periodontitis during pregnancy if oral hygiene is inadequate. Periodontal disease in pregnant women is associated with premature birth, low birth weight, and preeclampsia. Objective: To determine the level of women of childbearing age regarding oral health during pregnancy at the Makassar District Health Center, East Jakarta. Research Methods: This type of research is analytic with a cross-sectional research design. The number of respondents in this study was 101 respondents using a purposive sampling method. Data collection was carried out through questionnaires and data were analyzed using the Chi-Square proportion test. Results: The results of the Chi-Square test between the level of knowledge of women of childbearing age regarding oral health during pregnancy based on age, occupation, and marital status showed insignificant results (p>0.05) while the results of the Chi-Square test based on education level, SES, and history of pregnancy showed significant results (p<0.05). Conclusion: Most women of childbearing age, who visit the Makassar sub-district health center, East Jakarta, have low knowledge about oral health during pregnancy. The knowledge of women of childbearing age at the Makassar district health center, East Jakarta, is related to their education background, SES, and history of pregnancy.